2015
DOI: 10.1002/cam4.409
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the microRNA miR‐433 promotes resistance to paclitaxel through the induction of cellular senescence in ovarian cancer cells

Abstract: Annually, ovarian cancer (OC) affects 240,000 women worldwide and is the most lethal gynecological malignancy. High-grade serous OC (HGSOC) is the most common and aggressive OC subtype, characterized by widespread genome changes and chromosomal instability and is consequently poorly responsive to chemotherapy treatment. The objective of this study was to investigate the role of the microRNA miR-433 in the cellular response of OC cells to paclitaxel treatment. We show that stable miR-433 expression in A2780 OC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
90
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(101 citation statements)
references
References 49 publications
4
90
0
Order By: Relevance
“…The present data, along with an analysis of a published dataset (27), showed that miR-433 was overexpressed in osteosarcoma tissues and cell lines. In combi nation with previous reports revealing the roles of miR-433 in various other types of cancer, including ovarian and gastric cancer (28,29), the present study further confirmed that miR-433 functions as an oncomiR in osteosarcoma. Furthermore, overexpression of miR-433 was shown to decrease the apoptosis of osteosarcoma cells by targeting PDCD4 in vitro.…”
Section: Discussionsupporting
confidence: 89%
“…The present data, along with an analysis of a published dataset (27), showed that miR-433 was overexpressed in osteosarcoma tissues and cell lines. In combi nation with previous reports revealing the roles of miR-433 in various other types of cancer, including ovarian and gastric cancer (28,29), the present study further confirmed that miR-433 functions as an oncomiR in osteosarcoma. Furthermore, overexpression of miR-433 was shown to decrease the apoptosis of osteosarcoma cells by targeting PDCD4 in vitro.…”
Section: Discussionsupporting
confidence: 89%
“…Expression of miR-433 was normalized using U6 RNA (for RNA from cells and tissues) and with Caenorhabditis elegans miR-39 mimic (for RNA from culture supernatant and serum samples) which was used as an RNA spike-in. Specific primers for miR-433, U6 and C. elegans miR-39 RNA were obtained from RiboBio (15,19). In total, three individual experiments were performed.…”
Section: Reverse Transcription-quantitative Polymerase Chain Reactionmentioning
confidence: 99%
“…miR-433 has been identified as a cancer-associated miRNA in various types of tumor, including bladder cancer, ovarian cancer, gastric cancer, hepatocellular carcinoma and oral squamous cell carcinoma (13)(14)(15)(16)(17). Furthermore, aberrant expression levels of miR-433 have been identified to be associated with chemosensitivity and enhanced survival of ovarian cancer cells (15,18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have demonstrated that miRNAs can perform oncogenic or tumor suppressive roles in various types of cancers. Previous studies have demonstrated the functional roles of miR-433 in several types of cancer, including retinoblastoma (10), ovarian cancer (11), bladder cancer (11), oral squamous cell carcinoma (OSCC) (12), gastric cancer (13), hepatocellular carcinoma (HCC) (14) and lung cancer (15). The downstream targets of miR-433 have been revealed to be strongly associated with cancer development, including Notch1, cAMP responsive element binding protein 1 (CREB1), paired box protein Pax-6 (PAX6), histone deacetylase 6 (HDAC6), kirsten rat sarcoma viral oncogene homolog and hepatocyte growth factor receptor (c-Met) (10,12,13,16 4 and CHANGSHENG YE to be downregulated in these cancer types, and miR-433 was demonstrated to function as a tumor suppressor by inhibiting cell proliferation, migration and differentiation (10,(12)(13)(14)16).…”
Section: Introductionmentioning
confidence: 99%